Prognostic Significance of Diffuse Large B-Cell Lymphoma Cell of Origin Determined by Digital Gene Expression in Formalin-Fixed Paraffin-Embedded Tissue Biopsies - Scott, David W; Mottok, Anja; Ennishi, Daisuke; Wright, George W; Farinha, Pedro; Ben-Neriah, Susana; Kridel, Robert; Barry, Garrett S; Hother, Christoffer; Abrisqueta, Pau; Boyle, Merrill; Meissner, Barbara; et al. (Journal of clinical oncology, 2015)
To evaluate the prognostic impact of cell-of-origin (COO) subgroups, assigned using the recently described gene expression-based Lymph2Cx assay in comparison with International Prognostic Index (IPI) score and MYC/BCL2 coexpression status (dual expressers). Reproducibility of COO assignment using the Lymph2Cx assay was tested employing repeated sampling within tumor biopsies and changes in reagent lots. The assay was then applied to pretreatment formalin-fixed paraffin-embedded tissue (FFPET) biopsies from 344 patients with de novo diffuse large B-cell lymphoma (DLBCL) uniformly treated with rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) at the British Columbia Cancer Agency. MYC and BCL2 protein expression was assessed using immunohistochemistry on tissue microarrays. The Lymph2Cx assay provided concordant COO calls in 96% of 49 repeatedly sampled tumor biopsies and in 100% of 83 FFPET biopsies tested across reagent lots. Critically, no frank misclassification (activated B-cell-like DLBCL to germinal center B-cell-like DLBCL or vice versa) was observed. Patients with activated B-cell-like DLBCL had significantly inferior outcomes compared with patients with germinal center B-cell-like DLBCL (log-rank P < .001 for time to progression, progression-free survival, disease-specific survival, and overall survival). In pairwise multivariable analyses, COO was associated with outcomes independent of IPI score and MYC/BCL2 immunohistochemistry. The prognostic significance of COO was particularly evident in patients with intermediate IPI scores and the non-MYC-positive/BCL2-positive subgroup (log-rank P < .001 for time to progression). Assignment of DLBCL COO by the Lymph2Cx assay using FFPET biopsies identifies patient groups with significantly different outcomes after R-CHOP, independent of IPI score and MYC/BCL2 dual expression.